Narrative evocations of school managers about management knowledge and practice policies - Morais, Joelson de Sousa (2020)
In this article we analyze the process of continuing education of school managers during the years 2015, 2016 and 2017 in the municipalities of Codó, São João do Sóter and Olinda Nova, as a research problem: what curricular knowledge and policies are woven into the narratives of school managers in the process of continuing education? The objective was: to understand what knowledge and curricular policies are woven into the narratives of school managers in basic education. The research approach is qualitative, using as methodological devices the written narrative and participant observation with 10 (ten) school managers, who were selected within a larger scope for their experiences and longer time in school management. As educators and teacher trainers that we are, and that we dialogue in the research with managers also trained in pedagogy, we arrive at the results that the managers’ narratives point to their knowledge, policies and practices arising from their daily work, as a result of their needs, expectations and desires, and thus create curricula that reveal potential for transformation and that alert for substantial changes in the organization and development of pedagogical work in the school context. The conclusions elucidate experiences that establish democratic management policies that are built in the school culture where managers develop pedagogical work and that become an indispensable way of consolidating public, democratic and social quality education.